Identifikasi Bentuk dan Karakteristik Rumah Tradisional Desa Bungaya, Karangasem, Bali: Identifikasi Bentuk dan Karakteristik Rumah Tradisional Desa Bungaya, Karangasem, Bali - A.A. Ngurah Aritama; I Wayan Wiryawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2020)
Bungaya village is one of the ancient Balinese villages that has a heritage in the form of a traditional settlement environment. As part of the settlement, traditional houses in the village of Bungaya have developed in their physical form and function. This research will explain the identification of forms and characteristics of traditional houses in Bungaya village. The method used in this research is qualitative with descriptive and exploratory approaches. The results of this study are in the form of pictures of traditional house layouts and their development over time. Based on the results of the study, it was found that there had been a change in physical form and the addition of new functions besides housing in traditional houses in Bungaya village, Karangasem Regency. Keywords: Identification; Form; Traditional house, Bungaya village